Haploinsufficiency of the TDP43 ubiquitin E3 ligase RNF220 leads to ALS-like motor neuron defects in the mouse. (2nd January 2021) - Ma, Pengcheng; Li, Yuwei; Wang, Huishan; Mao, Bingyu
Abstract: TDP43 pathology is seen in a large majority of amyotrophic lateral sclerosis (ALS) cases, suggesting a central pathogenic role of this regulatory protein. Clarifying the molecular mechanism controlling TDP43 stability and subcellular location might provide important insights into ALS therapy. The ubiquitin E3 ligase RNF220 is involved in different neural developmental processes through various molecular targets in the mouse. Here, we report that the RNF220 +/− mice showed progressively decreasing mobility to different extents, some of which developed typical ALS pathological characteristics in spinal motor neurons, including TDP43 cytoplasmic accumulation, atrocytosis, muscle denervation, and atrophy. Mechanistically, RNF220 interacts with TDP43 in vitro and in vivo and promotes its polyubiquitination and proteasomal degradation. In conclusion, we propose that RNF220 might be a modifier of TDP43 function in vivo and contribute to TDP43 pathology in neurodegenerative disease like ALS.